Anthropogenic VOCs in Abidjan, southern West Africa: from source quantification to atmospheric impacts - P. Dominutti; P. Dominutti; S. Keita; S. Keita; J. Bahino; J. Bahino; A. Colomb; C. Liousse; V. Yoboué; C. Galy-Lacaux; E. Morris; L. Bouvier; et al. (Atmospheric Chemistry and Physics, 2019)
Several field campaigns were conducted in the framework of the Dynamics-Aerosol-Chemistry-Cloud Interactions in West Africa (DACCIWA) project to measure a broad range of atmospheric constituents. Here we present the analysis of an unprecedented and comprehensive dataset integrating up to 56 volatile organic compounds (VOCs) from ambient sites and emission sources. VOCs were collected on multi-sorbent tubes in the coastal city of Abidjan, Côte d'Ivoire, in winter and summer 2016 and later analysed by gas chromatography coupled with flame ionization and mass spectrometer detectors (GC-FID and GC-MS) at the laboratory. The comparison between VOC emission source profiles and ambient profiles suggests the substantial impact of two-stroke motorized two-wheel vehicles and domestic fires on the composition of Abidjan's atmosphere. However, despite high VOC concentrations near-source, moderate ambient levels were observed (by factors of 10 to 4000 lower), similar to the concentrations observed in northern mid-latitude urban areas. Besides photochemistry, the reported high wind speeds seem to be an essential factor that regulates air pollution levels in Abidjan. Emission ratios (ΔVOC∕ΔCO) were established based on real-world measurements achieved for a selected number of representative combustion sources. Maximum measured molar mass emissions were observed from two-wheel vehicles, surpassing other regional sources by 2 orders of magnitude. Local practices like waste burning also make a significant contribution to VOC emissions, higher than those from light-duty vehicles by 1.5 to 8 orders of magnitude. These sources also largely govern the VOC's atmospheric impacts in terms of OH reactivity, secondary organic aerosol formation (SOAP), and photochemical ozone creation potential (POCP). While the contribution of aromatics dominates the atmospheric impact, our measurements reveal the systematic presence of anthropogenic terpenoids in all residential combustion sectors. Finally, emission factors were used to retrieve and quantify VOC emissions from the main anthropogenic source sectors at the national level. Our detailed estimation of VOC emissions suggests that the road transport sector is the dominant source in Côte d'Ivoire, emitting around 1200 Gg yr−1 of gas-phase VOCs. These new estimates are 100 and 160 times larger than global inventory estimations from MACCity or EDGAR (v4.3.2), respectively. Additionally, the residential sector is largely underestimated in the global emission inventories, by factors of 13 to 43. Considering only Côte d'Ivoire, these new estimates for VOCs are 3 to 6 times higher than the whole of Europe. Given the significant underestimation of VOC emissions from the transport and residential sectors in Côte d'Ivoire, there is an urgent need to build more realistic and region-specific emission inventories for the entire West African region. This might be true not only for VOCs, but also for all atmospheric pollutants. The lack of waste burning, wood fuel burning and charcoal burning, and fabrication representation in regional inventories also needs to be addressed, particularly in low-income areas where these types of activities are ubiquitous sources of VOC emissions.